Performance of Foreign Exchange Operation of Private Commercial Banks: A Case on Southeast Bank Limited - Islam, K. M. Anwarul (Asian Finance & Banking Review, 2017)
The banking sector is participating in many events on a daily basis. Conversely, the process of banking is become faster, simpler, and more universal all at the same time. They're constantly coming up with various ideas and products to meet customer demand. Banks and other financial services organizations all search for service improvement opportunities in order to gain a competitive advantage in the financial sector. As a result, every person has a banking procedure they should know about. In accordance with their goal, Southeast Bank Limited believes in building together towards tomorrow. To accomplish the goal of getting more customers, the bank demonstrates excellence in all stages while also fostering continual development. With this fast changing competitive climate, banks' strategic plans and networking will help them keep pace with the competition. The overall objective of this research had represented the foreign exchange performance of import, export and foreign remittance of Southeast Bank Limited. This paper examined about import, export and remittance performances have been analyzed and find out some problems relating to foreign exchange activities. Finally this research finished with some possible recommendation and concluding remark of the study.